Growth of boron doped hydrogenated nanocrystalline cubic silicon carbide (3C-SiC) films by Hot Wire-CVD. (April 2016) - Pawbake, Amit; Mayabadi, Azam; Waykar, Ravindra; Kulkarni, Rupali; Jadhavar, Ashok; Waman, Vaishali; Parmar, Jayesh; Bhattacharyya, Somnath; Ma, Yuan‐Ron; Devan, Rupesh; Pathan, Habib; Jadkar, Sandesh
Graphical abstract: Highlights: Boron doped nc-3C-SiC films prepared by HW-CVD using SiH4 /CH4 /B2 H6 . 3C-Si-C films have preferred orientation in (1 1 1) direction. Introduction of boron into SiC matrix retard the crystallanity in the film structure. Film large number of SiC nanocrystallites embedded in the a-Si matrix. Band gap values, E Tauc and E 04 ( E 04 > E Tauc ) decreases with increase in B2 H6 flow rate. Abstract: Boron doped nanocrystalline cubic silicon carbide (3C-SiC) films have been prepared by HW-CVD using silane (SiH4 )/methane (CH4 )/diborane (B2 H6 ) gas mixture. The influence of boron doping on structural, optical, morphological and electrical properties have been investigated. The formation of 3C-SiC films have been confirmed by low angle XRD, Raman spectroscopy, X-ray photoelectron spectroscopy (XPS), Fourier transform infra-red (FTIR) spectroscopy and high resolution-transmission electron microscopy (HR-TEM) analysis whereas effective boron doping in nc-3C-SiC have been confirmed by conductivity, charge carrier activation energy, and Hall measurements. Raman spectroscopy and HR-TEM analysis revealed that introduction of boron into the SiC matrix retards the crystallanity in the film structure. The field emission scanning electron microscopy (FE-SEM) and non contact atomic force microscopy (NC-AFM) results signify that 3C-SiC film contain well resolved, large number of silicon carbide (SiC) nanocrystallites embedded in the a-Si matrix having rms surface roughness ∼1.64 nm. Hydrogen content in doped films are found smaller than that of un-doped films. Optical band gap values, E Tauc and E 04 decreases with increase in B2 H6 flow rate.